Development of problem based learning for online tutorial program in plant development using Gibbs' reflective cycle and e-portfolio to enhance reflective thinking skills. Issue 2 (February 2019) - Sekarwinahyu, M; Rustaman, N Y; Widodo, A; Riandi, R
Abstract: Reflective thinking skill is needed by prospective and in-service teachers. A study about developing problem based learning for online tutorial program using Gibbs' reflective cycle and e-portfolio was conducted to enhance reflective thinking skills of biology education students who participated in Plant Development. Development research used in this study was conducted through preliminary study, program development, trial of the program, program revision, and program implementation. This paper will discuss about the results of the program development and the trial of the program that were conducted in 2017. The Program development is conducted through program design development, instrument development, validation of program design and instrument by experts, and program development based on the revised program design. The trial of the program is conducted three times with different strategies to see which strategy is the most effective to be implemented. Based on the results of expert's validation, research results show that the design of programs and instruments can be used as references in the development of the program with some improvements. Based on the trial of the program, the results obtained that the program needs to be improved in terms of setting access between sub-initiation and between initiations.